Biomechanical and Physiological Analyses of a Luggage-Pulling Task - HALLBECK, M. Susan; JUNG, Myung-Chul; HAIGHT, Joel M. (Industrial Health, 2007)
The purpose of this study was to identify the degree of physical stresses on two-wheeled carry-on luggage users in terms of biomechanics and work physiology. Based on 3D kinematics, a 3D inverse dynamic biomechanical model having fifteen segments was developed to evaluate a one-hand pulling task. Joint reaction forces, joint moments and physiological variables (energy expenditure and heart rate) were measured from four subjects who performed 32 luggage-pulling tasks on a doublewide treadmill in the configurations of handle height (100 cm and 110 cm), handle rotation (0° and 90°), pole angle (0° and 10°), wheel diameter (8 cm and 15 cm), load weight (15 kg or 23 kg), center of mass (low and middle), carpeting (no and yes), trial day (first and second) and subject height (short and tall). ANOVA revealed that wheel diameter, center of mass and subject height were highly associated with the physical stresses of luggage users, especially their right arm. Although the task seems light work, users should place heavy belongings at the bottom of luggage when packing and manufacturers should give a priority to large wheels for ergonomic design.